Metabolic Rescue of “Glucose Addicted” Cancer Cells In Vitro - Paolo Vignali (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
Transformations in the glycolytic metabolism of neoplasms modulate their robust cellular division. This characteristic leads to an “addiction” to glucose for continued proliferation and viability. This study investigated whether glucose metabolites could rescue cellular viability in glucose-starvation conditions, a model of the inter-tumoral nutrient-deficient environment. Findings illustrated potential cellular viability rescue with pyruvate addition in glucose-deprived conditions, yet the same potential was not observed with lactic acid, a metabolite that exists at characteristically high concentrations within the intertumoral microenvironment. These results could implicate a predominance of certain metabolic pathways in nutrient-starved cells. Molecular transport capacities across plasma membranes are tied closely to the effects of metabolites within the cell; therefore, the role of the MCT/CD147 transporter complex in lactic acid oxidation was investigated and was found to noticeably enhance this metabolic pathway.
Keywords: Cancer; Glucose; Neoplasms